2012
DOI: 10.1155/2012/574923
|View full text |Cite
|
Sign up to set email alerts
|

QT Prolongation Complicated with Torsades de Pointes in Prosthetic Mitral Valve Endocarditis: A Case Report

Abstract: We present the case of a 49-year-old male patient with prosthetic mitral valve endocarditis associated with QT prolongation and torsades de pointes. He was asymptomatic until the end of January 2012, when he was admitted to our hospital emergency unit because of syncope, fever, and suspicion of endocarditis. Cardiologic evaluation was requested and the transthoracic (TTE) and transesophageal (TEE) echocardiograms revealed vegetations on the prosthetic mitral valve. All cultures were positive for methicillin-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Accordingly, in a large cohort of 186 patients with myocarditis, Ukena et al ( 16 ) demonstrated that a QTc prolongation ≥440 ms was frequent (~25% of cases) and predicted a poor clinical outcome, including cardiac death. Moreover, several cases of marked QTc prolongation complicated with TdP have been reported in patients with acute infective carditis (myo/endocarditis), independently from the specific etiologic agent involved ( 45 57 ). A peculiar form of diffuse myocarditis is Chagas’s disease, triggered by the protozoan Trypanosoma cruzi , and then progressing for (auto)immune-mediated mechanisms ( 58 ).…”
Section: Inflammation As a Cause Of Acquired Lqtsmentioning
confidence: 99%
“…Accordingly, in a large cohort of 186 patients with myocarditis, Ukena et al ( 16 ) demonstrated that a QTc prolongation ≥440 ms was frequent (~25% of cases) and predicted a poor clinical outcome, including cardiac death. Moreover, several cases of marked QTc prolongation complicated with TdP have been reported in patients with acute infective carditis (myo/endocarditis), independently from the specific etiologic agent involved ( 45 57 ). A peculiar form of diffuse myocarditis is Chagas’s disease, triggered by the protozoan Trypanosoma cruzi , and then progressing for (auto)immune-mediated mechanisms ( 58 ).…”
Section: Inflammation As a Cause Of Acquired Lqtsmentioning
confidence: 99%
“…Other causes of acquired QT prolongation include cocaine abuse, myocardial ischemia, subarachnoid hemorrhage, stroke, autonomic neuropathy, HIV infection, and chronic renal disease requiring dialysis [Khan 2002;Familoni 2006;Yuan 2009]. The majority of cases are pause-dependent, characterized by bradyarrhythmia or sinus pause causing QT interval prolongation and arrhythmia [Tounsi 2012]. In the cases described herein, the development of torsades de pointes was preceded by bradyarrhythmias, characteristic of the pausedependent subtype of QT prolongation.…”
Section: Discussionmentioning
confidence: 86%
“…In cases of extension of infection into the cardiac septum, the conduction system may be affected, leading to arrhythmias [Mylonakis 2001]. Torsades de pointes is a form of polymorphic ventricular arrhythmia associated with QT interval prolongation [Tounsi 2012]. QT prolongation of 0.45 in males and 0.47 in females is diagnostic of long QT syndrome [Yuan 2009].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review of pubmed was done. We found cases of QT interval prolongation complicated with TDP in a prosthetic mitral valve endocarditis [6], in an IV drug abuse-associated IE [7], in a prosthetic mitral valve Brucella endocarditis complicated with TDP [8]. Interestingly our patient had a unique presentation: he was not an IV drug abuser, had no prosthetic valve, and the infective pathogen was enterococcus.…”
Section: Discussionmentioning
confidence: 91%